Cooperation and Mistrust in Relational Contracts - Holger Herz; Armin Schmutzler; André Volk (Center for Economic Studies and ifo Institute (CESifo), 2016)
Work and trade relationships are often governed by relational contracts, in which incentives for cooperative action today stem from the prospective future benefits of the relationship. In this paper, we study how reductions in clarity about the financial consequences of actions, induced by incomplete information about the costs of providing quality, affect relational contracts in buyer-seller relationships. Under incomplete information, payoffs to actions become private information. This can impede the joint understanding of what constitutes cooperative behavior, and may thus inject mistrust into relationships, even if credibility is held constant. Comparing seller-buyer relationships with and without complete information about seller costs in the laboratory, we find that such a lack of clarity has effects on the terms of relational contracts. However, these effects only concern the distribution of rents, and not efficiency.
Keywords: D01; D03; L14; L20; 330; relational contracts; incomplete information; experiments